Controlled oxidative ageing time of graphite/graphite oxide to graphene oxide in aqueous media - Duangdao Channei (2018)
© 2017, Australian Ceramic Society. The influence of different oxidative ageing times (12, 24 and 72 h) on the structural properties of graphene oxide (GO) was studied. Structural characteristics of GO were assessed by X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), zeta potential, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET) surface area analysis. Results showed that crystal structure of the (001) crystal plane of GO at 2θ = 12.13° was detected after oxidative ageing time of 72 h. No peak of the graphite oxide phase was observed indicating that the interlayer spacing was developed after complete exfoliation of the oxidised graphite oxide. The Raman spectra of the as-prepared GO treated for 72 h oxidative ageing exhibited strong D and G bands indicating the characteristic functional groups. The FTIR spectra of GO (72 h) confirmed the presence of multiple oxygen functional groups after the oxidation process which related to a net negative zeta potential surface charge. Morphology of the GO (72 h) revealed typical wrinkling and folding of the thin sheets. The BET surface area of GO treated for 72 h was measured at 1323.39 m 2  g −1 and the shape of the hysteresis loops (type IV isotherm) correlated with mesoporous materials.